Quality Control Analysis Using Six Sigma Method On BATA-SK34 Afterpress Product - Satoto, Handy Febri; Rifai, Muchamad Hakim (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
PT. PBA is a company that produces refractory bricks, refractory cement and monolithic refractory materials. Based on the results of observations at PT. PBA has 4 types of defects in SK-34 Brick products, namely lumps, cracks, inappropriate thickness, and stains. The highest number of defects occurred in Gumpil, namely 107. The aim of this research is to minimize product defects in Bata SK-34 by implementing six sigma steps, namely define, measure, analyze, improve, control (DMAIC). From the results of the analysis and research that has been carried out, a sigma value of 4.63 is obtained with a DPMO of 860.05. From the sigma value of 4.63 which is more than 4.5, it can be identified that the SK-34 Brick production process is still good. PT. PBA adalah perusahaan yang memproduksi batu bata tahan api, semen tahan api, dan bahan tahan api monolitik. Bedasarkan hasil pengamatan di PT. PBA terdapat 4 jenis kecacatan pada produk Batu Bata SK-34, yaitu gumpalan, retak, ketebalan yang tidak sesuai, dan noda. Jumlah kecacatan tertinggi terjadi pada gumpil, yaitu sebanyak 107 buah. Tujuan dilakukan penelitian ini adalah untuk meminimalisir adanya kecacatan produk pada Bata SK-34 dengan langkah-langkah penerapan six sigma yaitu define, measure, analyze, improve, control (DMAIC). Dari hasil analisis dan penelitian yang telah dilakukan, diperoleh nilai sigma sebesar 4,63 dengan DPMO sebesar 860,05. Dari nilai sigma sebesar 4,63 yang lebih dari 4,5 maka dapat diidentifikasi bahwa proses produksi Batu Bata SK-34 masih baik.